Marketing Strategy in The Development of Rira Dishwashing Soap and Clothes Washing Soap UMKM - Mitasari, Ratna; Nursabrina, Zata Yumni Subhati; Winarno, Agung (Pascasarjana Universitas Mataram, 2024)
The importance of MSMEs for the progress of a region, therefore the Sumber Kembar village apparatus agreed to provide direction to residents to be optimistic in running a business and not give up easily if they fail. The purpose of implementing this community service is to create a marketing strategy to improve MSMEs in the community environment. This activity was carried out at the Rira Liquid Soap and Laundry Dishwashing Soap community business, located in Junrejo sub-district, with several stages of activities including initial identification, analysis and planning, mentoring and implementation, and evaluation. The results of this study indicate that Community Service Activities at the